+0  
 
0
1153
2
avatar

If \(f(x)= [x+1/x-1]^3\) then f'(2)= ?

 

\(f'(x)= 3[x+1/x-1]^2\)just not sure what to do after that

 Oct 17, 2017
edited by Guest  Oct 17, 2017
edited by Guest  Oct 17, 2017
 #1
avatar+7348 
+1

Remember...

\(\frac{d}{dx}u^3 \,=\, 3u^2\,\cdot\,\frac{d}{dx}u\)

 

So

 \(f'(x)\,=\,3[x+\frac1x-1]^2\,\cdot\,\frac{d}{dx}[x+\frac1x-1] \\~\\ f'(x)\,=\,3[x+\frac1x-1]^2\,\cdot\,[\frac{d}{dx}x+\frac{d}{dx}\frac1x-\frac{d}{dx}1] \\~\\ f'(x)\,=\,3[x+\frac1x-1]^2\,\cdot\,[1-x^{-2}]\)

 

To find  f'(2) , plug in  2  for  x .

 

\(f'(2)\,=\,3[2+\frac12-1]^2\,\cdot\,[1-2^{-2}] \\~\\ f'(2)\,=\,3[\frac32]^2\,\cdot\,[1-\frac1{4}] \\~\\ f'(2)\,=\,3[\frac94]\,\cdot\,[\frac3{4}] \\~\\ f'(2)\,=\,\frac{81}{16}\)

 

 

( If   f(x)  is meant to be  \([\frac{x+1}{x-1}]^3\)  then you get a different answer. )

 Oct 18, 2017
 #2
avatar+17747 
+2

If  f(x)  =  [x + 1/x - 1]3,  f(x)  is of the form  f(x) = [g(x)]3, so  f'(x)  =  3[g(x)]2·g'(x)

  f(x)  =  [x + 1/x - 1]3     --->     f'(x)  =  3[x + 1/x - 1]3·[1 - 1/x2]

To find f'(2), replace x with 2 in the above derivative, and simplify.  

 Oct 18, 2017

18 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.